A genome-wide association study identifies genetic determinants of hemoglobin glycation index with implications across sex and ethnicity - House, John S.; Breeyear, Joseph H.; Akhtari, Farida S.; Evans, Violet; Buse, John B.; Hempe, James; Doria, Alessandro; Mychaleckyi, Josyf C.; Fonseca, Vivian; Shi, Mengyao; Li, Changwei; Liu, Shuqian; et al. (Frontiers in Endocrinology, 2024)
We investigated genetic determinants of variation in the hemoglobin glycation index (HGI), an emerging biomarker for risk of diabetes complications. We conducted genome-wide association analyses in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial (N=7,913) and formally replicated top findings in the Atherosclerosis Risk in Communities (ARIC) study. In ACCORD, we identified single nucleotide polymorphisms (SNPs) associated with HGI, including a peak with the strongest association at intergenic SNP rs73407935 (7q11.22) (P=5.8e-10) with local replication in ARIC. In black individuals, the variant rs10739419 on chromosome 9 in the Whirlin (WHRN) gene formally replicated (meta-P=2.2e-9). SNP-based heritability of HGI was 0.39 (P < 1e-10). Many HGI-associated SNPs were distinct from those associated with fasting plasma glucose or HbA1c, lending further support for HGI as a distinct biomarker of diabetes complications. HGI had significant sex-specific associations with SNPs in or near GALNT11 in women and HECW2 in men. Lastly, in Hispanic participants, we observed genome-wide significant associations with variants near USF1 and NXNL2/SPIN1. The results of the first evaluation of the genetic etiology of HGI indicate it is highly heritable and point to heterogeneity by sex and race.